2021
DOI: 10.1111/dth.15257
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the risk‐to‐benefit ratio of using cotrimoxazole as a pneumocystis pneumonia preventative intervention among pemphigus patients treated with rituximab: A retrospective study with 494 patients

Abstract: Rituximab is widely used as the first‐line treatment for pemphigus patients. Since it depletes the B cells, it increases the risk of infections. Here, we evaluated the prophylactic efficacy of cotrimoxazole in decreasing the risk of pneumocystis pneumonia (PCP) infection in the pemphigus patients treated with rituximab. The medical records of confirmed pemphigus patients receiving rituximab were evaluated in two groups; those who received cotrimoxazole as a prophylactic after rituximab and patients who only re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Besides screening infections before starting glucocorticoid treatment(28, 29), monitoring infection during treatment especially in high-risk patients as known before, our study provided probable infection predictive cutoff values of glucocorticoid dose and suggested combining other immunosuppressive agents to decrease the risk of infection. Preventive therapy had not been shown necessary (30)…”
Section: Discussionmentioning
confidence: 99%
“…Besides screening infections before starting glucocorticoid treatment(28, 29), monitoring infection during treatment especially in high-risk patients as known before, our study provided probable infection predictive cutoff values of glucocorticoid dose and suggested combining other immunosuppressive agents to decrease the risk of infection. Preventive therapy had not been shown necessary (30)…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of some safety concerns, such as increasing the risk of infection, although it seems much safer than conventional treatments, preventing the disease relapse has remained an issue. 24,25 Rituximab acts through depletion of CD20 positive cells, which covers a broad spectrum of B cells. Depending on several factors, repopulation of B cells could occur usually within 6 to 9 months in most cases, although it takes a longer time to reach the normal number of total CD20+ B cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is effective and not only could induce disease remission in most of the patients, it keeps the patients in the remission phase for a relatively long time on or off minimal therapy. Regardless of some safety concerns, such as increasing the risk of infection, although it seems much safer than conventional treatments, preventing the disease relapse has remained an issue 24,25 . Rituximab acts through depletion of CD20 positive cells, which covers a broad spectrum of B cells.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that there is no consensus on the need for prophylaxis due to the low incidence of PCP complications in these patients, and it is not mandatory to treat all pemphigus patients with rituximab. 58 …”
Section: Fungal Infections and Immunobiological Therapymentioning
confidence: 99%